Developmental patterns of sex differences in delinquency among African American adolescents: A test of the sex-invariance hypothesis - Jang, Sung Joon (Journal of quantitative criminology, 1995)
This paper addresses a developmental issue concerning longitudinal patterns of sex differences in delinquency. Hirschi and Gottfredson argue that the age-delinquency relation is invariant across sex and that sex differences in delinquency are invariant over time as well. A combination of these two propositions generates a hypothesis, called here the sex-invariance hypothesis, that sex differences in delinquency are invariant over developmental stages of adolescents. To test the sex-invariance hypothesis, nine waves of panel data collected from a representative urban sample of African American adolescents are analyzed. The overall findings show that sex differences in delinquency tend to vary as the subjects grow older, rather than remain constant as the invariance thesis posits. Specifically, sex differences in delinquency peak at the age of 15 and thereafter declines with age. We also find that parental supervision significantly explains sex differences in delinquency for younger adolescence, but not for older adolescence.